A BRIEF KNOWLEDGE OF BANAFSHA (VIOLA ODORATA LINN.) & OTHER VIOLA SPECIES - Asheesh, Kandpal; Suresh, Chaubey; Meenakshi, Pandey (International Journal of Ayurveda and Pharma Research, 2017)
All over the world Viola genus in the Violet family Violaceae is broadly distributed. It is the largest genus in the family containing 500 species. Products isolated from them as are- Essential oils, Glycosides (Iridin, Violaquercitrin, Violutoside), Carbohydrate (Inulin), Ester (Methyl salicylate), Mustard oil (Phenyl ethyl), Colouring matters (Luteolin, Quercetin) etc. Importance of Violaceae family in traditional medicines has been mentioned. Many medicinal herbs used for therapeutic applications such as act as blood purifier, treatment of bruises, ulcers, respiratory infections, renal disorders etc belong to this family. Viola odorata also known as sweet violet & it is a rich source of vitamin c. Traditionally is very much effective in jaundice, anti-inflammatory, anti-pyretic, anti bacterial, hepato-protective activity. Viola odorata syrup made from flower petals improves cough suppression in children with asthma. Intranasal administration of Viola odorata extract oil is sedative to the brain and is helpful in insomnia suffering patients. A Unani medicine named as Joshanda used in form of decoction for cough & colds contain this valuable herb. In Chinese system of medicine it has been prescribed against Cancerous growth. In France Viola syrup is used as cough remedy. Cultivation of Violets in England occurs largely Startford-upon-Avon for syrup formation, which when mixed with Almond oil used as laxative in children. In olden time it was believed that Viola flowers are beneficial for eyes. Traditional knowledge when tested Pharmacologically & Phyto-chemically it will give us new effective therapeutic agents. This article is compilation of different aspect of Viola odorata and other Viola species such as their botanical classification, morphological feature, geographical distribution, chemical constituents, pharmacological properties and ethno-medicinal uses.